The comparative development of elevated resistance to macrolides in community-acquired pneumonia caused by Streptococcus pneumoniae - Yayan J (Dove Medical Press, 2014)
Josef Yayan Department of Internal Medicine, Division of Pulmonary, Allergy and Sleep Medicine, Saarland University Medical Center, Homburg/Saar, Germany Background: Community-acquired pneumonia (CAP) is an acute inflammation of the lungs, which is often caused by Streptococcus pneumoniae. CAP is the leading cause of death by infectious disease in industrialized countries. Therefore, an immediate and effective antibiotic therapy is of great importance for the nonfatal outcome of the disease. The literature contains increasing data about the development of resistance to antibiotics that are used for the treatment of CAP caused by S. pneumoniae; this article also examines the possible development of resistance to antibiotics in S. pneumoniae in recent years.Methods: Within the study period of 2004–2014, all hospital charts from patients with CAP caused by S. pneumoniae were collected from the Department of Internal Medicine, Saarland University Medical Center, Homburg/Saar, Germany. The tracheal secretions of S. pneumoniae in CAP patients were obtained by bronchoalveolar lavage; bronchial aspirates were obtained through flexible bronchoscopy and directly from sputum, and blood cultures were examined microbiologically for microorganisms.Results: From a total of 100 patients with CAP caused by S. pneumoniae, 23 (53.49% [34.78% female], 95% confidence interval, 38.58–68.4) patients with a mean age of 59.78±15.77 years met the inclusion criteria of this investigation. These patients were compared to a total of 20 (46.51% [35% female], 95% confidence interval, 31.6–61.42) patients with a mean age of 58.9±13.36 years with CAP who were infested with S. pneumoniae. In the latter group, the streptococcal antigen was detected in pulmonary aspirations by bronchoscopy or in urine using polymerase chain reaction and a rapid pneumococcal test. Penicillin G and vancomycin had a high rate of sensitivity on the antibiogram for S. pneumoniae, which was obtained by bronchoalveolar lavage, bronchial aspirates through flexible bronchoscopy, and directly from sputum. Even though the rates obtained were without statistical significance, S. pneumoniae had a high resistance to macrolides, namely erythromycin, in patients with CAP. Macrolides, specifically erythromycin (17.39%) and azithromycin (4.35%) and other classes of antibiotics such as tetracycline (4.35%), had a statistically significant resistance to streptococcal pneumonia in patients with CAP (P=0.0009).Conclusion: Increased resistance was found for macrolides and tetracycline in patients with CAP by S. pneumoniae. Keywords: drug-resistant Streptococcus pneumoniae, drug-resistant antibiotics, antimicrobial therapy, pneumococcal pneumonia, penicillin resistance